S645C Point Mutation Suppresses Degradation of EGFR to Promote Progression of Glioblastoma - Huang, Wenda; Zou, Ling; Hao, Zhaonian; Wang, Baofeng; Mao, Feng; Duan, Qiuhong; Guo, Dongsheng (Frontiers in Oncology, 2022)
Abstract background The tightly controlled activity of EGFR is important for the homeostasis of self-renewal of human tissue. Mutations in the extracellular domain of EGFR are frequent and function as a novel mechanism for oncogenic EGFR activation in GBM, and impact the response of patients to small-molecule inhibitors. Methods We constructed glioblastoma cell lines stably expressing wild-type EGFR and mutant of EGFR S645C. We detected the growth of the cells in vitro and in vivo. And we evaluated the anti-tumor activity and effectiveness of gefitinib and osimertinib to the cells. Result In the present study, we identified an oncogenic substituted mutation of EGFR—S645C. The mutation can promote the proliferation and colony formation of glioblastoma in vitro and in vivo. Mechanistically, EGFR S645C mutation potentially changes the formation of hydrogen bonds within dimerized EGFR and inhibits the degradation of EGFR to prolong the downstream signalings. And the mutation induces resistance to gefitinib but presents an opportunity for osimertinib treatment. Conclusion The study indicated a novel oncogenic mutation and advises on the precise treatment of individual patients with EGFR S645C mutation.